First Report of Subcutaneous Phaeohyphomycosis of the Foot Caused by Phoma minutella - Baker, J. G.; Salkin, I. F.; Forgacs, P.; J. H. Haines; Kemna , M. E. (Journal of Clinical Microbiology, 1987)
Phoma minutella, a dematiaceous hyphomycete, was isolated to the exclusion of all other fungi from a subcutaneous inflammatory process on the foot of a farmer undergoing corticosteroid therapy for myasthenia gravis. Isolation was achieved on several nutrient media. Examination of stained smears and sections revealed dematiaceous fungal elements consistent with the mold. This is the first reported association of P. minutella with a human infection and only the second reported case involving a Phoma sp. as the etiologic agent of a subcutaneous infection.
Keywords: biology